Respuesta :

Answer:

x = 0, 2π/3, 4π/3

Step-by-step explanation:

2 cos(2x) − 2 cos x = 0

Use double angle formula.

2 (2 cos²x − 1) − 2 cos x = 0

Simplify.

4 cos²x − 2 − 2 cos x = 0

2 cos²x − 1 − cos x = 0

2 cos²x − cos x − 1 = 0

Factor.

(cos x − 1) (2 cos x + 1) = 0

Solve.

cos x = 1 or -½

x = 0, 2π/3, 4π/3

To solve this problem, we have to use trigonometric function in which we can use some trigonometric equations on this. The solutions to this equation is

[tex]\pi , \frac{\pi}{3}, \frac{5\pi}{3}[/tex]

Trigonometric Functions

We would apply a simple mathematical rule here;

[tex]a(b+c)=ab+ac[/tex]

Let's substitute our functions and solve

[tex]2cos(2x)+2cosx=0\\2(2cos^2x-1)+2cosx=0\\4cos^2x-2+2cosx=0\\2cos^2x+cosx-1=0\\2cos^2x=2cosx-cosx-1=0\\2cos^2x+cosx-1=0\\[/tex]

We can solve the quadratic equation and get a solution to this problem.

[tex](cosx+1)(2cosx-1)=0[/tex]

Using factorization method,

[tex]cosx+1 = 0\\cosx = -1\\x = cos^-^1(-1)\\x = \pi[/tex]

The second solution is

[tex]2cosx-1=0\\2cosx=1\\cosx=\frac{1}{2} \\x = cos^-^1(\frac{1}{2} \\x = \frac{\pi}{3}, \frac{5\pi}{3}[/tex]

From the above calculations, the solutions to this equation is

[tex]\pi , \frac{\pi}{3}, \frac{5\pi}{3}[/tex]

Learn more on trigonometric functions here;

https://brainly.com/question/2437614

#SPJ2

ACCESS MORE